Photochemistry of Polycyclic Hydrocarbons in cosmic Water Ice - Barros, Ana L. F. de (Cadernos de Astronomia, 2024)
This work encompasses the study of the photochemistry of molecules that have a large number of carbons and hydrogens (CnHm), known as polycyclic aromatic hydrocarbons (PAH). We will present the results obtained by irradiating with ultraviolet (UV), ice mixtures, at low temperatures, of the order of 15K, of the coronene molecule (C24H12 ) with water (H2 O), in different concentrations of Cor:H2O of (1:50), (1:150), (1:200), (1:300) and (1:400), using the technique Fourier Transform Infrared (FTIR) spectroscopy. We find that PAHs and their photoproducts in water, PAH:H2 O, induced by UV irradiation, have mid-infrared spectroscopic signatures in the 5–8 μm region contributing to the interstellar ice components described as C1 –C5. Our results suggest that water-rich oxygenated and hydrogenated PAHs may be in important regions of the interstellar medium.